Facile synthesis of Fe-based metal–organic frameworks from Fe2O3 nanoparticles and their application for CO2/N2 separation - Le, Van Nhieu; Tran, Hoai Duc; Nguyen, Minh Tien; Truong, Hai Bang; Pham, Toan Minh; Kim, Jinsoo (Beilstein Journal of Nanotechnology, 2024)
A facile approach was employed to fabricate MIL-100(Fe) materials from Fe2O3 nanoparticles through a conventional hydrothermal reaction without the presence of HF and HNO3. Effects of trimesic acid content in the reaction system on the quality and CO2/N2 separation performance of the as-prepared MIL-100(Fe) samples were investigated. Using 1.80 g of trimesic acid in the reaction system yielded the sample M-100Fe@Fe2O3#1.80, which proved to be the optimal sample. This choice struck a balance between the amount of required trimesic acid and the quality of the resulting material, resulting in a high yield of 81% and an impressive BET surface area of 1365.4 m2·g−1. At 25 °C and 1 bar, M-100Fe@Fe2O3#1.80 showed a CO2 adsorption capacity of 1.10 mmol·g−1 and an IAST-predicted CO2/N2 selectivity of 18, outperforming conventional adsorbents in CO2/N2 separation. Importantly, this route opens a new approach to utilizing Fe2O3-based waste materials from the iron and steel industry in manufacturing Fe-based MIL-100 materials.
Keywords: CO2/N2 separation; Fe2O3 nanoparticles; hydrothermal reaction; IAST-predicted CO2/N2 selectivity; MIL-100(Fe)